Training of Mathematics Olympiad Contents by Using Edmodo App for Mathematics Teachers of MGMP of Junior High School in Bukittinggi City - Arnellis Arnellis; Nonong Amalita; Elita Zusti Jamaan; Media Rosha; Saddam al Aziz (Fakultas MIPA Universitas Negeri Padang, 2021)
The purpose of this study is to improve the ability of mathematics olympiad coaches through the edmodo platform, and to find out the satisfaction of Bukittinggi junior high school mathematics teachers in fostering mathematics olympiads with the edmodo application. The target audience for the service is mathematics teachers in the Subject Teachers' Consultation (MGMP) at Bukittiggi Junior High School Mathematics. This training stage begins online with workshops from home, giving out questionnaires, administering tests, then followed by giving Edmodo platform skills, strengthening math olympiad training materials, and offline discussion sessions in the Edmodo class. The results of the training implementation showed that the mastery of Mathematics teachers in junior high schools in Bukittinggi City on the Olympic material through the tests given on the Edmodo platform was 76%, meaning that teachers who participated in this activity were able to conduct mathematics Olympiad coaching with the Edmodo application. While the results of the participant satisfaction questionnaire were 81.27% participants had good satisfaction with the training activities carried out.